PENGARUH BOARD DIVERSITY, KOMPENSASI DEWAN DIREKSI DAN KEPEMILIKAN MANAJERIAL DEWAN DIREKSI TERHADAP NILAI PERUSAHAAN - Marrieda Testarossa Pradana; Khairusoalihin Khairusoalihin (ANALISIS, 2021)
This study aims to determine the effect of the proportion of women in the board of directors, educational background of the board of directors and independent directors and compensation of the board of directors and managerial ownership on company value in goods and consumer sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2015 - 2019. The research population used is manufacturing companies in the goods and consumption sectors listed on the Indonesia Stock Exchange for the period 2015–2019. The method in this study uses proposive sampling. With this method, the number of samples in this study was obtained as many as 9 companies. The analytical tool of this study uses multiple linear regression. The results of the study show that (1) partially the educational background of the board of directors has a negative and significant effect on firm value, independent directors have a positive and significant effect on firm value, (2) while the proportion of women in directors, board compensation and managerial ownership has no effect. significant towards firm value, (3) simultaneously the proportion of women on the board of directors, educational background of the board of directors, independent directors, compensation for the board of directors and managerial ownership have a significant effect on firm value.